Kedudukan Hasil Tes DNA dalam Penetapan Status Hukum Anak Luar Nikah - Ulum, Muh. Bachrul (Fakultas Syariah IAIN Purwokerto, 2009)
Marriage law states that the descent of somebody can only be approved by birth certificate or decision from a Religious Court, based on sufficient evidences. DNA as one evidence is a blue print which explains the blood relation that can be descended to the next generation. However, the validity of this test is still hesitated. It is because the test is still insufficient as a powerful proof which can be used in courts.